Моделі та методи розв’язування нечітких задач дискретної оптимізації у діагностичних інформаційних технологіях - Sergienko, I. V.; Parasyuk, I. N.; Kaspshitskaya, M. F. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The paper considers discrete optimization methods for a number of models of practically important covering, choice and clusterization problems appearing in designing and operation of diagnostic information technologies in fuzzy space. General and specific statements of such problems are given and solution methods are considered for them. On the basis of the T. Saati hierarchy analysis method, an approach is also proposed for calculation of weight coefficients for creation of additive objerlive and constraining functionals.